PENGARUH PEMBELAJARAN DARING PADA MATERI TATAK MENABI PAGE UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN KELAS X MAN BATU BARA - Sa’bani, Nadiatul; Heniwaty, Yusnizar (Gesture: Jurnal Seni Tari, 2022)
ABSTRACT - This study aims to describe the effect of online learning on the Tatak Menabi Page material to increase the effectiveness of learning in class X MAN Batu Bara. The theory used is online learning theory (Jaya Kumar: 2002), learning effectiveness theory (Nana Sudjana: 1990) and learning steps (Anitah: 2017). The research method used is quantitative methods with an experimental approach. The entire population of class X MAN Batu Bara and the sample of class X IPA 1 students was 36 students. Data collection techniques in the form of observations / observation sheets, test learning outcomes, documentation and relevant research. The research instrument was multiple choice questions totaling 20 questions which were first tested for validation, as well as observation sheets on attitudes and the learning process. Before the action is taken, a pre-test is given to measure students' initial abilities. From the results of the evaluation before and after the application of the media, the pre-test data for cognitive realm showed that the average value obtained was 39.17 (none of the students reached the KKM). After the application of online learning media, the average score was 74.58 (14 students reached the KKM). From the results of the pre-test and post-test there was an increase of 39%. This shows that there is an effect of online learning on the Tatak Menabi Page material to increase the effectiveness of learning in class X MAN Batu Bara at cognitive realm by 39%.  In psychomotor realm, the pre-test scores obtained by 2 students reached the KKM and after being given online learning media, the post-test scores of 2 students reached the KKM scores, this shows that no change has occurred in other words there is no effect of online learning on the Tatak Menabi Page material. to improve the effectiveness of class X MAN Batu Bara learning. Keyword: Online Learning, Learning Effectiveness, Tatak Menabi Page.      ABSTRAK - Penelitian ini bertujuan untuk mendeskripsikan pengaruh pembelajaran daring pada materi Tatak Menabi Page untuk meningkatkan efektivitas pembelajaran kelas X MAN Batu Bara. Teori yang digunakan adalah teori pembelajaran daring (Jaya Kumar : 2002), teori efektivitas pembelajaran (Nana Sudjana : 1990) dan langkah-langkah pembelajaran (Anitah : 2017). Metode penelitian yang digunakan metode kuantitatif dengan pendekatan eksperimen. Populasi seluruh siswa kelas X MAN Batu Bara dan sampel siswa kelas X IPA 1 berjumlah 36 siswa. Teknik pengumpulan data berupa observasi/lembar pengamatan, tes hasil belajar, dokumentasi dan penelitian relevan. Instrument penelitian yaitu soal- soal pilihan berganda berjumlah 20 soal yang terlebih dahulu di uji validasi, serta  lembar pengamatan sikap dan proses pembelajaran.  Sebelum dilakukan tindakan terlebih dahulu diberikan pre-test untuk mengukur kemampuan awal siswa. Dari hasil evaluasi sebelum dan sesudah diterapkannya media diperoleh data pre-test untuk ranah kognitif menunjukan bahwa nilai rata-rata yang diperoleh adalah 39,17 (tidak ada siswa yang mencapai KKM). Setelah diterapkannya media pembelajaran daring diperoleh nilai rata-rata 74,58 (14 siswa mencapai KKM). Dari hasil pre-test dan post-test terjadi peningkatan sebesar 39%. Hal ini menunjukan ada pengaruh pembelajaran daring pada materi Tatak Menabi Page untuk meningkatkan efektivitas pembelajaran kelas X MAN Batu Bara pada ranah kognitif sebesar 39 %. Pada ranah psikomotorik nilai  pre-test diperoleh 2 siswa mencapai KKM dan setelah diberikan media pembelajaran daring diperoleh nilai post-test 2 siswa mencapai nilai KKM, hal ini menunjukan tidak ada perubahan yang terjadi dengan kata lain tidak ada pengaruh pembelajaran daring pada materi Tatak Menabi Page untuk meningkatkan efektivitas pembelajaran kelas X MAN Batu Bara. Kata kunci : Pembelajaran Daring, Efektivitas Pembelajaran, Tatak Menabi Page.